Money Supply, Stock Prices and the Efficient Market Hypothesis: The Case of Malaysia (Malaysian Management Journal, 1999)
The purpose of the present study is to investigate the empirical relationships between money supply and stock prices in the Kuala Lumpur Stock Exchange (KLSE) using monthly data that span from January 1978 to September 1992. More specifically, we tested market informational efficiency in the KLSE by testing the causal relationships between money supply and stock prices using the co-integration technique. In the analysis, we used alternative monetary aggregates namely, the Simple-Sum and Divisia monies. Results from- our error-correction model suggest that market informational efficiency hypothesis can be rejected for KLSE with respect to the growth of money supply (for both Simple-sum and Divisia monetary aggregates).